ANALISIS UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM TERKAIT PERSYARATAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) TERHADAP HAK POLITIK MASYARAKAT ADAT - Ginting, Bagas Audi; Firdausy, Adriana Grahani (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
The purpose of this study is to determine the problems faced by Indigenous Peoples on Electronic Resident Identity Cards (e-KTP) as a condition in exercising their right to vote in general elections and their resolution. The results showed that article 348 paragraph (9) has the potential to eliminate the suffrage of indigenous peoples who are constrained by recording e-KTPs because they live in remote areas. The article was then submitted for constitutional testing to the Constitutional Court and decided in the Constitutional Court Decree Number 20/PUU-XVII/2019 that article 348 paragraph (9) contradicted the constitution. The issuance of this decision cannot immediately resolve the problems of indigenous peoples in guaranteeing their right to vote. Affirmative Action is a solution in solving these problems in the form of policies such as changing perspectives and approaches in identifying barriers to voting rights, synchronizing population data and granting NIK to indigenous peoples.